Auditor Professionalism: Management Performance Analysis in Corporate Financial Reporting - Aditya Riky Nugroho (Journal of Accounting Inquiry, 2022)
Purpose: Internal auditors are expected to have a high professionalism attitude that can encourage management performance in a positive direction. Therefore, the purpose of this study is to find out how the effect of auditor professionalism on management performance and in the company's financial reporting. Methodology : The research method used is explanatory research method. The sample used in this study is an internal audit who works for companies and government agencies in the Jakarta area. Data were obtained using a questionnaire that was distributed directly and compiled using a Likert scale. The data obtained were analyzed descriptively. The research data were analyzed using descriptive statistical techniques, testing data quality by conducting internal consistency tests and construct validity tests, as well as classical assumption tests, namely multicollinearity, autocorrelation and heteroscedasticity. To test the hypothesis used linear and stratified regression techniques using the SPSS statistical program. Findings: Based on the research data, it can be concluded that there is a positive influence between auditor professionalism on performance management in the company's financial reporting system. Novelty: The previous study focused on organizational and professional commitment on the job satisfaction of accountants. This study tries to examining how internal audit professionals relate to financial reporting management.   Keywords: Auditor, Performance Management, Financial Report